A methodology for building acoustics assessment and classification, in Portugal - Patrício, J. (2011)
This paper presents a methodology to assess the overall acoustics quality of buildings, thus contributing for their classification in terms of acoustic comfort, and consequently in their acoustic sustainability. The proposed methodology, which is expected to be implemented in the near future in Portugal, relies on two main evaluations: one related to buildings integration into the near environment (planning context); and other on the acoustic performance of their partitions, level of noise from service equipment, partitioning of rooms relatively to one another, and different usages available inside the buildings (i. e. apartments versus shops). Three examples of this methodology implementation are presented in the paper, and some conclusions are extracted from the achieved results in close elation to the principles of buildings global sustainability.